Analisis Isozim untuk Mengetahui Variasi Genetik Sebagai Upaya Pemurnian Ras Sapi Aceh - Armansyah, Teuku; -, Al-Azhar; Siregar, Tongku Nizwan (Jurnal Veteriner, 2012)
This study was performed to investigate genetic variation of Aceh’s cattle based on analysis of malatedehydrogenase (MDH) and esterase isozymes. Blood samples were collected from 30 out of 345 Aceh’scattles raised at the Center for Breeding Prime Animals (BPTU) of Indrapuri, Aceh Besar. The phenotypecharacteristics of each cattle were recorded before blood collection, and then analyzed based on theRegulation of Agricultural Minister of Indonesia No. 54/permentan/ot.140/10/2006 whereas isozymesanalysis was done by vertical acrylamide gel electrophoresis under constant current of 10 mA at 4°C for 4hours and appropriate staining systems. The pattern band which showed the genotype of the testedcattles, were then used as the basis to determinate the heterozygosity and proportion of polymorphic locus.The results showed that phenotype variation was found among Aceh’s cattle raised at the BPTU Indrapuri,Aceh Besar. Two locus detected in this research were MDH 1 and MDH2, whereas esterase locus (Est1 andEst2) were not detected due to the unsuccesful of the electrophoresis. MDH1 and MDH2 loci in the redblood cells of Aceh’s cattle were polymorphic. On the basis of malate dehydrogenase isozymes usingMVSP 3.1 Program and Simple Matching Coefficient it could be concluded that there was individualgenetic variation among Aceh’s cattles raised at the BPTU Indrapuri, Aceh Besar.
Keywords: isozyme, aceh cattle, malate dehydrogenase